Pathological and radiological irregularities in patients with chronic kidney disease - An observational study - Dushyant Pawar; Vinayak Bhoi; Pawar, Shital; Dilip Patil (Asian Journal of Medical Sciences, 2022)
Background: Chronic kidney disease (CKD) encompasses a spectrum of different pathophysiologic processes associated with abnormal renal function and progressive decline in glomerular filtration rate (GFR). Aims and Objectives: The objectives of the study are 1) to assess basic tests and kidney function tests in patients with CKD, (2) to assess coagulation profile, sugar levels, and platelets levels in patients of CKD, (3) to do the urine analysis in patients with CKD, and (4) to assess GFR among the study population. Materials and Methods: After taking the informed consent, detailed history was taken and clinical examination of patient was done. Pathological tests such as hemogram, renal function tests, liver function tests, coagulation profile, blood sugar levels, urine routine, and microscopy were performed. Ultrasonography of abdomen and pelvis was done. Correlation was done between severity of sepsis and mortality in patients. Results: Anemia was moderate (7–8.9 g/dl) in 38%, mild (9–10.9 g/dl) in 31%, while severe (<6.9) in 29 patients, that is, 29%. Thrombocytopenia was present in 58% of patients. Mean serum albumin in patients was 2.67±0.551 mg/dl; serum globulin was 3.89±0.345 mg/dl. Mean blood sugar of study subjects was 127.41±61.387 mg/dl fasting, 199.67±114.827 mg/dl post-prandial, and mean glycated hemoglobin was 5.63 ± 1.668. On ultrasound acute pyelonephritis, 25 (25%) was the most common finding. Conclusion: Correlation of clinical findings with pathological and radiological findings is very important in patients with CKD. Severity of sepsis directly correlates with mortality of patients.